Operative experience in essential emergency general surgery procedures: is autonomy achievable during surgical training?. Issue 6 (22nd March 2021) - Belvedere, Shane; Joh, Daniel; Furlong, Tim; Dennett, Elizabeth; Loveday, Benjamin P. T.
Abstract : This study assessed the experience and autonomy of general surgery trainees in New Zealand in 10 emergency general surgery procedures, and identified factors associated with reaching primary operator thresholds. Abstract: Background: Readiness for practice is an ongoing concern in surgery. Surgeons who have completed general surgery training are expected to be proficient in performing common emergency procedures. The aim of this study was to assess the experience and autonomy of general surgery trainees in New Zealand in 10 emergency general surgery procedures, and identify factors associated with reaching primary operator (PO) thresholds. Methods: Operative logbook data from all New Zealand general surgery trainees from 2013 to 2017 were analysed. Data for 10 emergency general surgery procedures were extracted to determine PO and autonomous PO (mentor not scrubbed) rates. A threshold of 70% for PO and APO rates was used to define two levels of proficiency. Results: A total of 120 trainees performed 40 865 included procedures. Trainees met the PO threshold for all procedures by Surgical Education and Training (SET) 5. The APO threshold was met for three of 10 procedures (appendicectomy, drainage of perianal abscess and perforated peptic ulcer repair). Final APO rates for the other procedures ranged from 18% to 58%. On multivariate analysis, SET year and case volume were associated with increased odds of meeting the PO and APO thresholds. Female trainees were less likely to reach the PO and APO thresholds for three of 10 and four of 10 procedures, respectively. Conclusion: Trainees had increasing PO and autonomous PO rates over the course of their training. Graduating New Zealand general surgeons likely have sufficient operative experience in emergency general surgery procedures. However, rates of autonomy are lower, and further research is needed to determine whether this affects readiness for independent practice.